Multiple pregnancy. Study at the National Hospital Cayetano Heredia - Gonzáles del Riego, Manuel (2015)
Two groups of patients were studied, 126 between 1979 and 1981 and 109 between 1994 and 1995, with similar characteristics. No significant differences were found with age of patients, parity, pregnancy induced hypertension, duration of gestation, newborn weight, but cesarean section and IUGR increased lately and newborns less than 1500 g decreased. Puerperal morbidity was higher with cesarean section. Maternal mortality was nil and perinatal mortality decreased, with prevalence of prematurity. Fetal mortality was 50% or more when less than 1000 g, but early neonatal mortality newborns less than 1500 g decreased from 80% to 46,7%.